In Situ Study of the High-Temperature Solid-Phase Synthesis of Zinc Tungstate in the Zinc Oxide–Tungsten Oxide System; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 18, iss. 6 - Mostovshchikov A. V. Andrey Vladimirovich; Tokarev D. S. Denis Sergeevich; Gubarev F. A. Fedor Aleksandrovich; Pirozhkov A. V. Alexey Vladimirovich; Tikhonov D. V. Dmitry Vladimirovich (2024, 2024)
Title screen